Tidewater Glaciers and Bedrock Characteristics Control the Phytoplankton Growth Environment in a Fjord in the Arctic - Halbach, Laura; Vihtakari, Mikko; Duarte, Pedro; Everett, Alistair; Granskog, Mats A.; Hop, Haakon; Kauko, Hanna M.; Kristiansen, Svein; Myhre, Per I.; Pavlov, Alexey K.; Pramanik, Ankit; Tatarek, Agnieszka; et al. (Frontiers in Marine Science, 2019)
Meltwater discharge from tidewater glaciers impacts the adjacent marine environment. Due to global warming tidewater glaciers are retreating and will eventually terminate on land. Yet, the mechanisms through which meltwater runoff and subglacial discharge from tidewater glaciers influence marine primary production remain poorly understood, as data in close proximity to glacier fronts are scarce. Here, we show that subglacial meltwater discharge and bedrock characteristics of the catchments control the phytoplankton growth environment inside the fjord, based on data collected in close proximity to tidewater glacier fronts in Kongsfjorden, Svalbard from 26 to 31 July 2017. In the southern part of the inner fjord, glacial meltwater from subglacial discharge was rich in fine sediments derived from erosion of Devonian Old Red Sandstone and carbonate rock deposits, limiting light availability for phytoplankton (0.6 mg m–3 Chl a on average, range 0.2-1.9 mg m-3). In contrast, coarser sediments derived from gneiss and granite bedrock and lower subglacial discharge rates were associated with more favourable light conditions facilitating a local phytoplankton bloom in the northern part of the inner fjord with mean Chl a concentration of 2.8 mg m-3 (range 1.3-7.4 mg m-3). In the northern part, glacier meltwater was a direct source of silicic acid through weathering of the silica-rich gneiss and granite bedrock. Upwelling of the subglacial freshwater discharge plume at the Kronebreen glacier front in the southern part entrained large volumes of ambient, nutrient-rich bottom waters which led to elevated surface concentrations of ammonium, nitrate and partly silicic acid. Total dissolved inorganic nitrogen transported to the surface with the upwelling of the subglacial discharge plume has a significant potential to enhance summer primary production in Kongsfjorden, with ammonium released from the seafloor being of particular importance. The transition from tidewater to land-terminating glaciers may, thus reduce the input of nutrients to the surface layer with negative consequences for summer productivity.